The Mad King - Burroughs, Edgar Rice, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 1995)
"The Mad King" by Edgar Rice Burroughs is a Ruritanian romance originally published in 1914-1915. Young American Barney Custer travels to the fictional European kingdom of Lutha, unaware he's the exact double of the newly escaped King Leopold. Mistaken for royalty, Barney becomes entangled in royal intrigue, falls for the king's promised bride Princess Emma, and must impersonate the monarch to save the throne from a scheming prince. Set against the outbreak of World War I, this adventure follows Barney through diplomatic danger, narrow escapes, and battles that will determine Lutha's fate. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Mad_King
Release date is 1995-11-01
Judith Boss
Keywords: Fantasy fiction; Impostors and imposture -- Fiction; Adventure stories; Kings and rulers -- Fiction; Mistaken identity -- Fiction